Mental wellbeing among Hispanic female domestic cleaners - Jennifer Ish; David Gimeno Ruiz de Porras; Kristina W. Whitworth (BMC, 2020)
Abstract Background The purpose of this study was to examine the mental wellbeing of self-employed, Hispanic female domestic cleaners in San Antonio, Texas. Methods We conducted a cross-sectional pilot study and administered a short questionnaire to 56 participants. Mental wellbeing was assessed using The World Health Organization Well-Being Index (WHO-5). We calculated the age-adjusted prevalence of poor mental wellbeing, both overall and stratified by socioeconomic, neighborhood, and health characteristics. Results Almost half of the participants screened positive for poor mental wellbeing (47.3%) with a mean WHO-5 score of 68.9 [standard error (SE) = 3.1]. We observed a high prevalence of poor mental wellbeing among participants with less than a high school education (56.0%), who worked less than 30 h per week (57.0%) and who sometimes or always felt unsafe at her cleaning job (69.1%). Conclusions Female domestic cleaners, particularly those who work in the informal sector, are an overburdened and understudied population. This is particularly true regarding their mental wellbeing, which has largely been considered as an afterthought in epidemiologic studies of cleaning workers in general. Our results suggest that this group of domestic cleaners faces several psychosocial stressors, both in and outside of the workplace, and may have a high risk of poor mental health outcomes.